PANCA JIWA AS SOCIAL CAPITAL APPROACH: AN ALTERNATIVE STARTEGY FOR ISLAMIC ECONOMIC DEVELOPMENT - Syamsuri Syamsuri; Yuwan Ebit Saputro (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
The economic issue is considered as a universal issue; one of the major problems in economy is the backwardness of economic development in rural areas. This study aims at seeking solutions using panca jiwa concepts of Pondok Gontor (sincerity, simplicity, self-sufficiency, Islamic brotherhood and freedom) as a social capital of the economic development in underdeveloped areas. This research employed a qualitative method as it is relevant in revealing details on the phenomenon. Data was gathered through interview, observation, and documentation. The collected data was then analyzed inductively and presented descriptively. The finding shows that the study area has a potent of panca jiwa, a potential to become an economic development strategy in solving poverty and underdevelopment which remained unsolved for decades.============================================================================================Pendekatan Panca Jiwa sebagai Modal Sosial: Suatu Strategi Alternatif dalam Pembangunan Ekonomi Islam. Masalah ekonomi dianggap sebagai masalah universal; salah satunya adalah keterbelakangan pembangunan ekonomi di daerah pedesaan. Penelitian ini bertujuan untuk mencari solusi terhadap permasalahan tersebut dengan menggunakan pendekatan panca jiwa dari Pondok Modern Gontor (keikhlasan, kesederhanaan, berdikari, ukhuwah Islamiyyah dan jiwa bebas) sebagai modal sosial dalam pembangunan ekonomi di daerah tertinggal. Metode kualitatif dipilih dalam penelitian ini karena relevansinya dalam mengungkapkan rincian tentang fenomena di lapangan. Data-data penelitian dikumpulkan melalui wawancara, observasi, dan dokumentasi. Data tersebut kemudian dianalisis secara induktif, dan disajikan secara deskriptif. Hasil penelitian menunjukkan bahwa wilayah studi memiliki potensi panca jiwa yang sangat kuat untuk menjadi strategi dalam pembangunan ekonomi untuk memecahkan kemiskinan dan keterbelakangan yang selama ini menjadi masalah yang belum terselesaikan.